Laparoscopic vs. Open Repair Surgery for the Treatment of Communicating Hydrocele in Children: A Retrospective Study From a Single Center - Liu, Jie; Tang, Rui; Wang, Xiao; Sui, Bangzhi; Jin, Zhiyuan; Xu, Xudong; Zhu, Qinghua; Chen, Jin; Ma, Honglong; Duan, Guangqi (Frontiers in Surgery, 2021)
Purpose: This study evaluated the outcomes of laparoscopic repair (LR) and open repair (OR) surgery for communicating hydrocele in children. Patients and Methods: We collected the clinical data and follow-up data of all boys (<14 years) who underwent communicating hydrocele surgery in the pediatric surgery department at Yijishan Hospital of Wannan Medical College from January 2017 to December 2018 and retrospectively analyzed the data. Results: In this study, 155 patients were retrospectively enrolled, including 90 patients in the OR group and 65 patients in the LR group. There were significant differences in operation time and the recurrence of hydrocele between the two groups. The persistence of scrotal swelling in the LR group was significantly lower than that in the OR group. There was no significant difference in postoperative hospitalization time or incision infection rate between the two groups. Conclusion: In conclusion, this study shows that laparoscopic treatment of children with communicating hydrocele has the advantages of a hidden incision, a shortened operation time, and a reduced postoperative recurrence rate and can be used as the preferred surgical method. However, laparoscopic treatment should be selected according to the specific condition of each child and cannot completely replace traditional open surgery.